2008
DOI: 10.1002/ibd.20336
|View full text |Cite
|
Sign up to set email alerts
|

Fecal S100A12 and fecal calprotectin as noninvasive markers for inflammatory bowel disease in children

Abstract: Both fecal markers were superior to the sensitivities and specificities of any standard inflammatory test. Both fecal S100A12 and calprotectin are sensitive markers of gastrointestinal inflammation, but fecal S100A12 provided exceptional specificity in distinguishing children with IBD from children without IBD. Fecal S100A12 is a simple, noninvasive test that can be used to screen and select children warranting further invasive and laborious procedures such as endoscopy for the investigation of their gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 34 publications
(44 reference statements)
7
149
3
1
Order By: Relevance
“…Sidler et al 82 compared FC with faecal S100A12, CRP and ESR. S100A12 is a protein from the same S100 family as calprotectin (which is a complex of S100A8 and S100A9).…”
Section: Results Of Clinical Effectiveness Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Sidler et al 82 compared FC with faecal S100A12, CRP and ESR. S100A12 is a protein from the same S100 family as calprotectin (which is a complex of S100A8 and S100A9).…”
Section: Results Of Clinical Effectiveness Reviewmentioning
confidence: 99%
“…However, this cannot be the sole explanation, because raised calprotectin levels have been reported in studies that exclude people using NSAIDs. 60,82 As noted in a previous assessment report for NICE, some people with IBS-D may have bile acid malabsorption.…”
Section: Inflammatory Irritable Bowel Syndrome?mentioning
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that an inflammatory mediator directly released into the gut lumen from the inflammatory process might be an ideal test to detect bowel inflammation in IBD (19). In many studies, fecal calprotectin has been claimed to be a specific, sensitive, non-invasive, cheap and accessible marker for gut inflammation (11,12,17). The fact that calprotectin is stable in room temperature for 5 days makes it more suitable for routine clinical studies (20).…”
Section: Figurementioning
confidence: 99%
“…It is present in neutrophils and monocytes and is released by activation of these cells in plasma, urine, stools and other media as a consequence of disease activity (9). Several studies reported that fecal calprotectin (FC) level is associated with invasive markers of gut inflammation such as 99Tc-labeled white cell scans and endoscopic and histologic inflammation scores (10).Recent studies showed FC is a specific, sensitive, non-invasive, cheap and accessible marker for gut inflammation (11)(12). The aims of the present study were to evaluate the clinical value of fecal calprotectin as a non invasive marker in differentiating organic from functional bowel diseases in correlation with endoscopic and histopathological examinations in Egyptian patients.…”
Section: Introductionmentioning
confidence: 99%